Answer:
Step-by-step explanation:
We are to prove the cofunction Identity using the Addition and Subtraction Formulas. [tex]tan(\pi/2 - u) = cot (u)[/tex]
From trigonometry identity, [tex]tan x = sinx/cosx[/tex], starting from right hand side of the equation, the expression above will become;
[tex]tan(\pi/2 - u) = \dfrac{sin(\frac{\pi}{2}-u )}{cos(\frac{\pi}{2}-u) }........ \ 1 \\\\from\ quadrant;\\\\sin(\frac{\pi}{2}-u) = cos (u) \ and \ cos(\frac{\pi}{2}-u) = sin(u)[/tex]
Substituting this trigonometry identities into equation 1 we will have;
[tex]tan(\pi/2 - u) = \dfrac{cos(u)}{sin(u)}[/tex]
Since cot(u) = 1/tan(u) = cos(u)/sin(u), hence;
[tex]tan(\pi/2 - u) = \dfrac{cos(u)}{sin(u)} = cot(u)\\\\tan(\pi/2 - u) = cot (u)\ Proved![/tex]